National Survey on Music Practices in Canada - Barbeau, Audrey-Kristel; Héroux, Isabelle; Ryan, Gina; Thouin-Poppe, Louis-Édouard (Intersections, 2022)
The COVID-19 pandemic significantly impacted musical practices in Canada and had a major effect on the lives of musicians. The aim of this study was to document the profile of Canadian musicians aged 14 and over who participated in a national survey on the effects of musical practice on well-being, mental health, and social support during the first half of 2022 (Barbeau et al., 2024). It also examined their musical development, access to school-based music education, musical habits, and how their engagement with music evolved during the pandemic. A total of 1,619 Canadian musicians completed the survey, which revealed a fairly diverse demographic profile, though slightly skewed toward younger generations, individuals identifying as female, living in large urban centers, and of predominantly European descent. The vast majority had access to music in school. Most respondents reported practicing music several times a week or daily, and in various forms (such as solo or ensemble playing). These types of musical engagement evolved in response to pandemic-related restrictions. This study offers a snapshot of the Canadian musical landscape as it stood in 2022 and highlights the richness and diversity of musical backgrounds and experiences across the country.